ANALISIS WACANA SARA MILLS DALAM FILM ANIMASI â€œPEMIMPIN PEREMPUANâ€ KARYA CISFORM UIN SUKA - Meirianti, Mike; choiriyati, Sri; Amirullah, Muhammad ilyas (Universitas Muhammadiyah Lampung, 2024)
Film is an effective medium for providing entertainment and information to the public. as in the animated film